USE OF SILONITE INDIVIDUAL IRRIGATOR AND ITS EFFICACY IN TREATMENT OF PARODONTOPATHY - Bilokon, N.P.; Shevtsov, О.О.; Bilokon, S.О.; Mammadov, А.; Abdo, Х.; Bieliaiev, I.S. (World of Medicine and Biology, 2015)
The paper presents the findings of clinical studies of the effectiveness of using the individual irrigator Silonite in the treatment of periodontal disease. The analysis of the data determines the prospects for its use in the practice of dentistry with the conduct of thorough research in this direction.
Keywords: individual irrigator; parodontitis; gingivitis